Anticipated technology shocks: A re-evaluation using cointegrated technologies - Joel Wagner (Bank of Canada, 2017)
Two approaches have been taken in the literature to evaluate the relative importance of news shocks as a source of business cycle volatility. The first is an empirical approach that performs a structural vector autoregression to assess the relative importance of news shocks, while the second is a structural-model-based approach. The first approach suggests that anticipated technology shocks are an important source of business cycle volatility; the second finds anticipated technology shocks are incapable of generating any business cycle volatility. This paper challenges the latter conclusion by presenting a structural news shock model adapted to reproduce the cointegrating relationship between total factor productivity and the relative price of investment. With cointegrated neutral and investment-specific technology, anticipated shocks to the common stochastic trend explain approximately 22%, 32%, 34% and 20% of the variance of output, investment, hours and consumption in the United States, respectively, reconciling the discrepancy between theory and data.
Keywords: E32; 330; Business fluctuations and cycles; Productivity